INTEGRATED CONTROLLING APPROACHES AND THEIR IMPACT ON WORKING CAPITAL EFFICIENCY AND CORPORATE PROFITABILITY - Peter BAGDACS (Oradea Journal of Business and Economics)
This paper explores the relationship between controlling and working capital management in the context of increasingly globalized and dynamic economic environments. As companies face growing demands for timely and high-quality information from both internal and external stakeholders, the role of controlling has become more vital than ever in supporting managerial decision-making. The research question addresses how controlling approaches and systems contribute to the efficient use of working capital and, ultimately, corporate profitability. This is a theoretical and literature-based study, supported by numerous empirical findings cited in the literature, and it applies a qualitative analytical framework to examine various controlling models and their relevance in financial decision-making. Specifically, the paper compares major international controlling approaches – including the German coordination-oriented, the Anglo-Saxon performance-focused, the Scandinavian sustainability-integrated, and the Japanese efficiency-centered systems – emphasizing how each framework supports financial planning, monitoring, and performance optimization. Moreover, the paper focuses on the role of financial controlling in managing liquidity and cash flow, particularly through the lens of working capital components such as inventories, receivables, and short-term liabilities. Key financial indicators such as the Cash Conversion Cycle (CCC), Net Trade Cycle (NTC), Return on Assets (ROA), Gross and Net Operating Profits (GOP, NOP) are also presented to measure the efficiency of working capital use. The study concludes that efficient working capital management is strongly correlated with higher profitability, and highlights the trade-offs between liquidity and profitability that decision-makers must manage. The findings underscore the importance of implementing a hybrid, data-driven controlling system that incorporates precision, strategic alignment, sustainability, and continuous improvement, ensuring long-term competitiveness and financial stability in an uncertain economic landscape. This study will be especially relevant to financial managers, controllers, and organizational decision-makers seeking to align financial operations with broader corporate goals.